Influence of Irrigation and Nutrient Management on Fruit Quality in Banana 'Nendran' Under Precision Farming - Jaya, Shimi Gnanadasan; Rathnamma, Sheela Karunakaran (Asian Journal of Biological and Life Sciences, 2017)
The present investigation was carried out for two consecutive seasons from 15 February 2012 to 10 November 2013 in the Instructional Farm of College of Agriculture, Vellayani to study the effect of irrigation and nutrient management through fertigation and foliar nutrition on fruit quality in banana 'Nendran' under precision farming. The experiment was carried out in split plot design with six main plots and three sub plots, replicated thrice. Irrigation and nutrient management practices adopted under main plots included basin and drip irrigation with soil application of full dose of nutrients and drip fertigation using different water soluble fertilizers at 60 % of recommended dose. Foliar nutrition included 19-19-19 foliar spray, Sulphate of Potash (SOP) bunch spray and water spray. The study revealed that irrigation and nutrient management practices had significant influence on all quality attributes except TSS (Total Soluble Solids) and ascorbic acid content in banana fruits in both the years. Soil application of full dose of nutrients with drip irrigation, fertigation of 60 % of RDN (recommended dose of nutrients) as 10-10-10, urea and SOP and fertigation of 60 % of RDN as 13-0¬45, 0-0-50 and DAP (Diammonium Phosphate) were equally effective in enhancing total sugars, reducing sugars, non-reducing sugars and pulp-peel ratio. More over spraying with SOP in the bunches @ 2 % after complete bunch emergence and three weeks after first application significantly improved all fruit quality parameters.
Keywords: Banana; Fertigation; Foliar nutrition; Precision farming; Quality